Influence of different fuel agents on the combustion synthesis of the nanostructured Li1.05Mn2O4 oxide - Amaral,F. A. (2014)
In this work nanostructured Li1.05Mn2O4 oxide was obtained by Solution Combustion Synthesis (SCS) using three different fuel agents in order to obtain a unique phase with a crystalline cubic structure belonging to the Fd3m spatial group. The phase of interest could be obtained, following the order: glycine (at 600 °C for 2 h) < urea (at 750 °C for 2 h) < maleic anhydride (at 750 °C for 4 h), with crystallite size in the range from 4.6 to 9.7 nm (nanometric character) and the unit cell parameter of the calcined samples at 750 °C for 2 h were similar to the JCPDS 35-0782 with cubic structure (a = 8.247 Å). Charge and discharge tests from the samples obtained by glycine fuel (at 750 °C for 4 h) presented the highest experimental specific capacities of 115 mA h g-1 and 92% of retention after 10 cycles.